1998
DOI: 10.1017/s0021859698005310
|View full text |Cite
|
Sign up to set email alerts
|

The use of measurements of soil mineral N in understanding the response of crops to fertilizer nitrogen in intensive cropping rotations

Abstract: The effects on succeeding crops of nitrogen in residues returned to the soil of brassica vegetable crops (Brassica oleracea) were studied on a nitrogen-retentive silt loam soil at Horticulture Research International, Kirton, Lincolnshire, UK. A sequence of four crops was started in 1988 and again in 1989. In the first sequence, two successive cauliflower crops (Brassica oleracea cv. botrytis L.), crops 1 and 2 in the first year, were followed by Brussels sprouts (Brassica oleracea cv. Gemmifera D.C.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2000
2000
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 0 publications
0
12
0
1
Order By: Relevance
“…However, using the balance advisory system of the N-Expert system, N supply levels were simply recommended as 110, 155, and 250 kg N ha −1 for amaranth, spinach and cauliflower, respectively (Table 3). Rahn et al (1998) found no yield response Figure 1. Nitrogen uptake patterns of two field vegetable crops in comparison with estimated data from the N-Expert system (W1, conventional irrigation practice; W2, 50% to 80% of PESW; N1, conventional fertilizer N application rate; N2, fertilizer N recommendation from N-Expert system; predicted uptake by N-Expert system).…”
Section: Crop Growth and Nitrogen Uptakementioning
confidence: 95%
“…However, using the balance advisory system of the N-Expert system, N supply levels were simply recommended as 110, 155, and 250 kg N ha −1 for amaranth, spinach and cauliflower, respectively (Table 3). Rahn et al (1998) found no yield response Figure 1. Nitrogen uptake patterns of two field vegetable crops in comparison with estimated data from the N-Expert system (W1, conventional irrigation practice; W2, 50% to 80% of PESW; N1, conventional fertilizer N application rate; N2, fertilizer N recommendation from N-Expert system; predicted uptake by N-Expert system).…”
Section: Crop Growth and Nitrogen Uptakementioning
confidence: 95%
“…In the cabbage and cauliflower paddocks, some of the mineral N may have originated from the large amount of crop residues that was returned to the soil when the previous crop was harvested. The residues of these vegetable crops have low C:N ratios, so rapidly mineralise when incorporated into the soil (De Neve & Hofman 1998;Rahn et al 1998;Goulding 2000;Mitchell et al 2000). After winter leaching, mean soil profile mineral N contents were still significantly greater in the potato and greens paddocks than in the dairy paddocks (Table 1).…”
Section: Soil Mineral N Contentsmentioning
confidence: 99%
“…data). Consequently, the rapid mineralisation of residues from the previous greens crops may have contributed to the larger than expected nitrate leaching losses from the greens paddocks (De Neve & Hofman 1998;Rahn et al 1998;Goulding 2000;Mitchell et al 2001).…”
Section: Soil Solution Nitrate Concentrations and Nitrate Leaching Lomentioning
confidence: 99%
See 1 more Smart Citation
“…Such a model is also able to predict the amount of N in crop residues, which contain more than 50 % of total N uptake of cauliflower (Rahn et al 1992;. These large N residues may affect the N supply of a succeeding crop (Rahn et al 1998) and/or the possible N-losses through leaching (De Neve & Hofman 1998) and denitrification (Schloemer 1991).…”
Section: Introductionmentioning
confidence: 99%